WRITTEN CORRECTIVE FEEDBACKS USED BY ENGLISH TEACHERS OF THE STATE SENIOR HIGH SCHOOLS IN EFL WRITING CLASSES: A STUDY ON TEACHERS AND STUDENTS’ PERCEPTIONS ON THE MOST EFFECTIVE FEEDBACKS - ., I Komang Sesara Rakayana; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk (1) mengidentifikasi jenis umpan balik korektif tertulis digunakan oleh guru-guru di tiga SMA Negeri di Singaraja di kelas menulis, (2) mencari tahu apa yang guru pikir sebagai umpan balik yang paling efektif di antara jenis umpan balik korektif tertulis, dan (3) mencari tahu apa yang siswa pikir sebagai umpan balik korektif tertulis yang paling menguntungkan untuk peningkatan tulisan mereka. Penelitian ini melibatkan enam guru bahasa Inggris dan tiga belas anak kelas sebelas dari tiga SMA Negeri di Singaraja. Data penelitian ini berupa data pengamatan dan data wawancara. Data pengamatan dikumpulkan melalui pengamatan kelas dan tulisan-tulisan mahasiswa yang telah diperbaiki namun belum dikembalikan oleh guru, sedangkan data wawancara dikumpulkan melalui wawancara guru dan siswa. Semua data dianalisa secara deskriptif. Hasil penelitian ini menunjukkan bahwa umpan balik terintegrasi tampak mendominasi penggunaan. Para guru dan siswa memiliki persepsi yang beraneka mengenai masukan yang paling efektif dan menguntungkan, yang mencerminkan beberapa korespondensi dan perbedaan. Umpan balik secara lisan yang ditemukan dalam penggunaannya adalah jenis umpan balik formatif. Saran-saran diberikan terutama untuk guru bahasa Inggris dan Lembaga Kurikulum Pendidikan dan Pelatihan Guru.Kata Kunci : Umpan balik korektif, tulisan EFL, umpan balik efektif This study aimed at (1) identifying the types of written corrective feedback employed by the teachers in three state senior high schools in Singaraja in writing classes, (2) finding out what the teachers think as the most effective feedback among the types of written corrective feedback, and (3) finding out what the students think as the most beneficial written corrective feedback for their writing improvement. The study involved six English teachers and thirteen eleven graders from three state senior high schools in Singaraja. The data were in the forms of observation data and interview data. The observation data were collected through classroom observations and student writings which had been corrected but not returned yet by the teachers, while the interview data were collected through teacher and student interviews. The data were all analyzed descriptively. The results indicated that the integrated feedbacks seemed dominated the uses of written corrective feedback. The teachers and the students had varied perceptions on the most effective and beneficial feedbacks, which reflect some correspondences and discrepancies. Oral feedback found in use was the formative feedback. Suggestions were mainly provided for English teachers and the Curriculum of Teacher Training and Education Institution.keyword : Corrective feedback, EFL writing, effective feedback